Lao PDR - Mapping the Gender Dimensions of Trade : A Preliminary Exposition - World Bank (Washington, DC, 2012)
The Lao Government has also made important commitments to gender equality in both its national socio-economic development planning and in a number of international agreements. Through mapping the gender dimensions of trade in Lao PDR, this report aims to draw out key inter-linkages between a more open trade policy and gender. Recent export performance in Lao has been strong and mostly driven by hydro-electricity and minerals, which constituted more than half of all exports in 2010 and are predicted to grow even more in the next few years. To better understand the interaction between gender and trade policy, this paper presents a gender mapping exercise for export development in Lao PDR and in this regard presents simple recommendations on how to undertake this type of exercise. The paper is split in two parts: the first sketches out a simple methodological framework that can be used by researchers to do an initial mapping of the inter-relationships between export promotion/trade policy and gender. The second part of the paper is aimed primarily at policy makers. It uses the framework to provide a diagnostic which examines: 1) sectors in Lao with potential for export expansion that could benefit women; 2) gender-based constraints in these sectors which limit their expansion through trade; and 3) potential impacts for women, both positive and negative, from an increase in Lao's natural resource exports.